The Further Adventures of Newborn Screening for Biotinidase Deficiency: Where It Is at and What We Still Need to Know - Barry Wolf (MDPI AG, 2016)
Biotinidase deficiency is an inherited metabolic disorder that, if untreated, can result in neurological and cutaneous symptoms. If treated with the vitamin biotin, individuals with the disorder can markedly improve, but still may have some irreversible problems if therapy is delayed. If treated at birth, biotin therapy can prevent the development of symptoms as indicated by long-term outcomes. Therefore, the disorder readily meets the major criteria for newborn screening. Our laboratory has been instrumental in developing, piloting and establishing newborn screening for the disorder in the United States and in many countries. This review discusses some of the "behind-the-scenes" aspects of how we spread the word about the disorder and what we learned from over 30 years of newborn screening. We also discuss some of the controversies and issues about biotinidase deficiency that remain to be addressed. Based on the successful outcomes of older adolescents and adults with profound biotinidase deficiency identified by newborn screening, this is one of the best, if not the best, disorder for which to perform newborn screening. In summary, "If an individual has to have an inherited metabolic disorder, biotinidase deficiency is the one to have."